2021
DOI: 10.1111/anec.12903
|View full text |Cite
|
Sign up to set email alerts
|

Stress and autonomic nerve dysfunction monitoring in perioperative gastric cancer patients using a smart device

Abstract: Background Heart rate variability (HRV), a sensitive marker of stress and autonomic nervous disorders, was significantly decreased in cardiovascular disease, inflammation, and surgical injury. However, the effect of radical gastrectomy on HRV parameters needs to be further investigated. Methods A prospective, observational study including 45 consecutive enrolled patients undergoing radical gastrectomy in our enhanced recovery after surgery (ERAS) programs was conducted. Frequency‐ and time‐domain parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Therefore, several studies have reported that increased inflammatory indicators, such as the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C-reactive protein (CRP), are associated with cancer recurrence and poor prognosis following radical resection in many types of cancer, including GC [ 50 , 67 , 68 ]. When compared with levels before gastrectomy, inflammatory markers, including neutrophil percentage, CRP, procalcitonin (PCT) and plasma cortisol, were significantly increased after surgery [ 69 ]. These clinical findings indicate that gastrectomy and its associated events activate an inflammatory response, resulting in more recurrence after surgery.…”
Section: Mechanisms Underlying the Increased Recurrence Rate Resultin...mentioning
confidence: 99%
“…Therefore, several studies have reported that increased inflammatory indicators, such as the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C-reactive protein (CRP), are associated with cancer recurrence and poor prognosis following radical resection in many types of cancer, including GC [ 50 , 67 , 68 ]. When compared with levels before gastrectomy, inflammatory markers, including neutrophil percentage, CRP, procalcitonin (PCT) and plasma cortisol, were significantly increased after surgery [ 69 ]. These clinical findings indicate that gastrectomy and its associated events activate an inflammatory response, resulting in more recurrence after surgery.…”
Section: Mechanisms Underlying the Increased Recurrence Rate Resultin...mentioning
confidence: 99%
“…Heart rate variability is the beat-to-beat variability in heart rate, a sensitive marker of altered autonomic function, that is reduced under different stress conditions. 12 , 13 Many studies have reported decreased HRV indices after abdominal, 14 , 15 , 18 orthopedic, 10 and thoracic surgery, 17 , 19 demonstrating impaired autonomic regulation in the early postoperative period. Contrary to these studies, we found no significant changes during sleep in HRV indices of total autonomic power (SDNN, TP-i) after acute mild blood loss, showing an intact autonomic cardiovascular regulation and autonomic capacity, when blood loss is not associated with surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 13 Postoperative autonomic dysfunction with limited autonomic capacity and decreased sympathetic and parasympathetic outflow characterized by decreased HRV indices is a well-described pathophysiologic phenomenon after various major surgeries and is linked to postoperative morbidity and mortality. 10 , 14 20 …”
mentioning
confidence: 99%
“…One of the explanations for the lack of effect on long-term outcomes by SNS blockade is that in addition to increased levels of catecholamine, various inflammatory mediators are also abundantly released into circulation during cancer surgery. The levels of inflammatory mediators, including C-reactive protein (CRP), procalcitonin, prostaglandin E2 and plasma cortisol, were elevated significantly after gastrectomy[ 45 , 46 ]. Activation of the inflammatory response plays an important role in residual cancer cell survival and progression through humoral factor release or premetastatic niche establishment[ 47 - 49 ].…”
Section: Potential Perioperative Interventionsmentioning
confidence: 99%